Exploring the Nexus of E-Commerce and Tax Evasion: A Comprehensive Data Analysis - Effendi, Muhammad Imam; Mediawati, Noor Fatimah; Fidayanti, Anita Rohma (Proceedings of The ICECRS, 2023)
This dataset, compiled from 1523 documents retrieved via lens.org using "E-Commerce" and "Tax Evasion" keywords, focuses on the legal aspects of online business. After refining document types to "Journal Article" and "Conference Proceeding," 771 relevant documents were obtained. The goal was to create a resource aiding research into the intersection of E-Commerce and Tax Evasion. Employing document type filters ensured a refined dataset for scholars and researchers. Results yielded a comprehensive collection facilitating insights and further analysis in this domain. This dataset serves as a valuable tool for understanding the legal dimensions of online business practices and their implications regarding tax evasion.Highlights : Dataset comprising 771 documents on E-Commerce and Tax Evasion Facilitates in-depth research into the legal intersection of online business and tax evasion Valuable resource for scholars investigating the legal dimensions of E-Commerce practices Keywords: E-Commerce, Tax Evasion, Dataset, Legal Aspects, Online Business